2021
DOI: 10.1088/1741-2552/ac33e7
|View full text |Cite
|
Sign up to set email alerts
|

Decoding of cortex-wide brain activity from local recordings of neural potentials

Abstract: Objective. Electrical recordings of neural activity from brain surface have been widely employed in basic neuroscience research and clinical practice for investigations of neural circuit functions, brain–computer interfaces, and treatments for neurological disorders. Traditionally, these surface potentials have been believed to mainly reflect local neural activity. It is not known how informative the locally recorded surface potentials are for the neural activities across multiple cortical regions. Approach. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Given the correlation between the MUA power recorded from the surface and the cellular calcium signals imaged at 225 μm depth, we asked whether it is possible to predict the brain activity at deeper layers by only harnessing high-resolution electrical recordings from the cortical surface. To that end, we implemented a simple neural network model that consists of a linear hidden layer, a single-layer LSTM network, and a linear readout layer ( Figure 5a ) [22, 72]. The neural networks were trained to learn the nonlinear relationships between cellular calcium activities and surface potentials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the correlation between the MUA power recorded from the surface and the cellular calcium signals imaged at 225 μm depth, we asked whether it is possible to predict the brain activity at deeper layers by only harnessing high-resolution electrical recordings from the cortical surface. To that end, we implemented a simple neural network model that consists of a linear hidden layer, a single-layer LSTM network, and a linear readout layer ( Figure 5a ) [22, 72]. The neural networks were trained to learn the nonlinear relationships between cellular calcium activities and surface potentials.…”
Section: Resultsmentioning
confidence: 99%
“…To that end, we implemented a simple neural network model that consists of a linear hidden layer, a single-layer LSTM network, and a linear readout layer (Figure 5a) [22,72]. The neural networks were trained to learn the nonlinear relationships between cellular calcium activities and surface To evaluate the contributions spatially provided by different channels, we performed the decoding using subsets of channels starting from those closest to the FoV (Figure S7a).…”
Section: Predicting Neural Activity In Layer 1 and Layer 2-3 From Sur...mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies taking into account the related underlying state of cortical or thalamic neuronal populations demonstrated that these locally recorded signals themselves can predict whole brain activity ( 20 ) and functional connectivity ( 15 ). It has further been shown that local recordings of neuronal activity carry information that allows decoding of cortex-wide brain activity across modalities ( 76 ). We reported here that the two exemplary states, SWA and PA, differ regarding spatiotemporal characteristics on the local and global scales and show state-dependent propagation modes, which might explain these findings.…”
Section: Discussionmentioning
confidence: 99%